PENGARUH PERILAKU KELOMPOK NELAYAN TERHADAP KESEJAHTERAAN MASYARAKAT KAMPUNG NELAYAN MAJU (KALAJU) - Sarabiti, Rinaldi Eka Saputra; Nurhaeny, Andiah; Ruman, Rifyan (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Tanjung Air Panas Village, Negeri Tulehu, Salahutu District is one of two villages in Maluku that has Marine Stewardship Council (MSC) Certification by the Indonesian Ministry of Maritime Affairs and Fisheries, namely Waepure Village in Buru Regency and Air Panas Village, Negeri Tulehu Regency, Central Maluku Regency. The purpose of this study was to analyze the influence of fishermen's group behavior on the welfare of the Negeri Tulehu community and the policy directions needed to improve the welfare of fishermen's groups in Negeri Tulehu. This study is a quantitative study with a total sample of 45 respondents and was analyzed using Multiple Linear Regression Analysis and SWOT Analysis. Based on the results of the determination coefficient test (R2), it can be seen that the R Square value of 0.699 if it increases by one unit becomes 69.9%. The strategy is determined based on the results of the IFAS matrix analysis and the EFAS matrix to determine the position of the strategy to be implemented. The results of the SWOT analysis show that the position of fishermen in Tanjung Air Panas Village, Negeri Tulehu is in quadrant I (Aggressive strategy), this position is determined by looking at the strength value and opportunity value which are greater than the weakness value and threat value. The abstract is presented in Indonesian. The abstract consists of one paragraph with a maximum of 250 words. The abstract includes an introduction, objectives, methods, results and main conclusions in full. ABSTRAKDusun Tanjung Air Panas Negeri Tulehu Kecamatan Salahutu menjadi satu dari dua desa di Maluku yang meemiliki Sertifikasi Marine Stewardship Council (MSC) oleh Kementerian Kelautan dan Perikanan RI yakni Desa Waepure di Kabupaten Buru dan Dusun Air Panas Negeri Tulehu Kabupaten Maluku Tengah. Tujuan dari penelitian ini yaitu untuk menganalisis pengaruh perilaku kelompok nelayan terhadap kesejahteraan masyarakat Negeri Tulehu serta arahan kebijakan yang diperlukan untuk meningkatkan kesejahteraan kelompok nelayan di Negeri Tulehu. Penelitian ini merupakan penelitian kuantitatif dengan total sampel 45 responden dan dianalisis menggunakan Analisis Regresi Linier Berganda dan Analisis SWOT. Berdasarkan hasil uji koefisien determinasi (R2)dapat diketahui bahwa nilai R Square sebesar 0,699 apabila meningkat satu satuan maka menjadi 69,9%. Strategi ditentukan berdasarkan hasil analisis matriks IFAS dan matriks EFAS untuk menentukan posisi strategi yang akan dilaksanakan. Hasil analisis SWOT menunjukkan bahwa posisi nelayan di Dusun Tanjung Air Panas Negeri Tulehu berada pada kuadran I (Strategi agresif) posisi ini ditentukan dengan melihat nilai kekuatan dan nilai peluang yang lebih besar dibandingkan nilai kelemahan dan nilai ancaman.